2011
DOI: 10.1162/jocn.2011.21609
|View full text |Cite
|
Sign up to set email alerts
|

Dishabituation of Laser-evoked EEG Responses: Dissecting the Effect of Certain and Uncertain Changes in Stimulus Modality

Abstract: Abstract■ The repetition of nociceptive stimuli of identical modality, intensity, and location at short and constant interstimulus intervals (ISIs) determines a strong habituation of the corresponding EEG responses, without affecting the subjective perception of pain. To understand what determines this response habituation, we (i) examined the effect of introducing a change in the modality of the repeated stimulus, and (ii) dissected the relative contribution of bottom-up, stimulus-driven changes in modality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 60 publications
(69 reference statements)
11
74
0
Order By: Relevance
“…Indeed, a recent study suggests that the population response to expected and unexpected events may best be explained by a combination of prediction-and prediction-error-related responses (Egner et al, 2010). Generally, our findings are well in line with earlier work that has shown that probability can have large effects on early cortical processing in the auditory cortex, both in nonhuman (Ulanovsky et al, 2003) and human (Haenschel et al, 2000(Haenschel et al, , 2005Weiland et al, 2008;Valentini et al, 2011) primates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, a recent study suggests that the population response to expected and unexpected events may best be explained by a combination of prediction-and prediction-error-related responses (Egner et al, 2010). Generally, our findings are well in line with earlier work that has shown that probability can have large effects on early cortical processing in the auditory cortex, both in nonhuman (Ulanovsky et al, 2003) and human (Haenschel et al, 2000(Haenschel et al, , 2005Weiland et al, 2008;Valentini et al, 2011) primates.…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, the gammaband activity we observed may signal a "prediction error" response. This response should therefore not be confused with the expectancy state itself, which is expressed in the temporal structure of activity patterns before the appearance of stimuli (Engel et al, 2001;van Ede et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to determine which of these stimulus attributes are determinant in causing response habituation. In two subsequent experiments we showed that introducing a selective change in the sensory modality of the stimulus produced a significant dishabituation of the ERPs (Valentini et al 2011), whereas introducing a selective change in its spatial location did not (Torta et al 2012). These findings suggest that different attributes defining a stimulus are not equally effective in inducing a dishabituation of the ERP response.…”
Section: Leps: Saliency Vs Noveltymentioning
confidence: 87%
“…However, by exploring the LEP dishabituation triggered by introducing selective changes of stimulus location or modality (i.e., two of the four basic attributes defining a sensory stimulus) we showed that LEPs are highly sensitive to bottom-up, stimulus-driven factors such as novelty (Torta et al 2012;Valentini et al 2011). Importantly, the design of these previous experiments did not allow differentiating between the respective effects of novelty and saliency in determining LEP dishabituation.…”
mentioning
confidence: 90%
“…Mouraux et al 2011). Further evidence that the so-called pain-related brain responses are not specific for pain perception, but depend on presentation context and on stimulus predictability and novelty comes from the studies by Clark et al (2008), Iannetti et al (2008), Wang et al (2010) and Valentini et al (2011).…”
Section: 3mentioning
confidence: 99%